Investigation of In Vitro Antioxidant and Hemoglobin Antiglycation Effect of Roasted and Unroasted Argania spinosa L. Seed Oil from Morocco - Daoudi, Nour E.; Abdnim, Rhizlan; Elkhadraoui, Ghariba; Mekhfi, Hassane; Legssyer, Abdelkhaleq; Ziyyat, Abderrahim; Bnouham, Mohamed (Current Chemical Biology, 2023)
Background: Argania spinosa L. seed oil is a Moroccan endemic product that is used traditionally as an alternative treatment for diabetes. Objective: The present work aims to evaluate the hemoglobin antiglycation and the antioxidant effect of roasted (Roil) and unroasted (UnRoil) Argan seed oil in vitro. Methods: The antioxidant activity was evaluated by different methods (total antioxidant capacity by the ammonium molybdate, metal chelating activity, ferric reducing antioxidant power, 1, 1-diphenyl- 2- picrylhydrazyl free radical scavenging, and β-carotene bleaching test), and the protein antiglycation effect was tested using hemoglobin, in vitro. Results: The results showed that both oils possess an important antioxidant effect and the roasting process did not influence the total antioxidant capacity, metal chelating activity, and β-carotene bleaching test. Although, it significantly influences the antiradical activity of Argania spinosa L. seed oil (p < 0.05) with IC50; values of 21.47 ± 0.076 μg/mL for Roil and 4.01 ± 1.13 μg/mL for UnRoil. Besides, Roil and UnRoil it significantly inhibit the hemoglobin glycation activity, with IC50; values of 1.09 ± 0.31 and 0.16 ± 0.031 mg/ml respectively. Moreover, it was noted that UnRoil has a lower IC50; value than Roil, which means that UnRoil has a more potent activity than Roil (p < 0.05). Conclusion: Argania spinosa L. seed oil is an essential source of natural antioxidants and hemoglobin antiglycation that plays a key role in scavenging of free radicals and might be used for reducing the development of diabetic complications.
Keywords: in vitro